Development of Blended Learning Model Based on Constructivism of Conservation Value - Farliana, N; ., Widiyanto; Budi Mulyono, K (KnE Social Sciences, 2018)
The aim of the reserach is design and develop the Management Information System course using e-learning system at Economics Faculty UNNES. The aim detail to be achieved are (1) developing blended learning model based constructivism of conservation value, (2) measuring effectiveness of implementation developed learning model, and (3) knowing the benefits to be gained by implementation the learning model. This research is development research with quantitative and qualitative approach. The research started with problem identification, then compile research instrument in questionnaire, observation and documentation. The next step is data collection, then presentation and data analysis, and conclusions for last step. The effectiveness of the development learning model is 82.58%. The results are clarified by student’s response that the developed learning model is effectively implementation in Management Information System learning and give understanding to students. Benefits gained by implementation the learning model viewed from personal and group side is change of insight and behavior of students that lead to character of conservation value, and in outcome side is creativity of development product information management system, building their own knowledge by hooking with daily living conditions, and actualization through skills possessed. Keywords: blended learning, constructivism, conservation value